2010
DOI: 10.1007/s10468-010-9207-9
|View full text |Cite
|
Sign up to set email alerts
|

Strong Lefschetz Elements of the Coinvariant Rings of Finite Coxeter Groups

Abstract: For the coinvariant rings of finite Coxeter groups of types other than H 4 , we show that a homogeneous element of degree one is a strong Lefschetz element if and only if it is not fixed by any reflections. We also give the necessary and sufficient condition for strong Lefschetz elements in the invariant subrings of the coinvariant rings of Weyl groups.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
14
0
1

Year Published

2011
2011
2013
2013

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 8 publications
1
14
0
1
Order By: Relevance
“…In fact, the coinvariant algebra of the Weyl group is isomorphic to the cohomology ring of the corresponding flag variety. In [11] and [12], it has been shown that the coinvariant algebra of any finite Coxter group has the Lefschetz property and that the set of the Lefschetz elements is the complement of the union of the reflection hyperplanes except for type H 4 case. The determination of the set of the Lefschetz elements is still open for H 4 because of the computational complexity.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, the coinvariant algebra of the Weyl group is isomorphic to the cohomology ring of the corresponding flag variety. In [11] and [12], it has been shown that the coinvariant algebra of any finite Coxter group has the Lefschetz property and that the set of the Lefschetz elements is the complement of the union of the reflection hyperplanes except for type H 4 case. The determination of the set of the Lefschetz elements is still open for H 4 because of the computational complexity.…”
Section: Introductionmentioning
confidence: 99%
“…It should be added that the hard Lefschetz theorem is highly non-trivial: Hodge proved it over C using his theory of harmonic integrals (now called Hodge theory) and later Deligne proved it in characteristic p using a version of the Riemann hypothesis for varieties over finite fields; see [12] for more details. For noncrystallographic W, Theorem 1 has been verified by direct computation in types I 2 (m) and H 3 by Maeno, Numata and Wachi [11] and in type H 4 by Numata and Wachi [13]. Here also it should be added that the computations for type H in [11] and [13] are very large and are carried out using the computer algebra package Macaulay2.…”
Section: Introductionmentioning
confidence: 92%
“…For noncrystallographic W, Theorem 1 has been verified by direct computation in types I 2 (m) and H 3 by Maeno, Numata and Wachi [11] and in type H 4 by Numata and Wachi [13]. Here also it should be added that the computations for type H in [11] and [13] are very large and are carried out using the computer algebra package Macaulay2.…”
Section: Introductionmentioning
confidence: 92%
“…In general the coinvariant algebras of finite groups are not always isomorphic to the cohomology rings of any manifolds. Indeed the coinvariant algebras of non-crystallographic finite Coxeter groups are not isomorphic to the cohomology rings of any varieties, but have the Lefschetz properties ( [6], [9], [10], [13]). See [2], [3], [7], [13], [14], for the study of Lefschetz properties for wider classes of graded Artinian algebras.…”
Section: Introductionmentioning
confidence: 99%
“…x, y, x 2 , xy, y 2 , x 3 , x 2 y, xy 2 , y 3 , x4 , x 3 y, x 2 y 2 , xy3 , y 4 , x5 , x 4 y, x 3 y 2 , x 2 y 3 , xy4 , y 5 , x6 , x 5 y, x 4 y 2 , x 3 y 3 , x 2 y 4 , xy5 , y 6 , x7 , x 6 y, x 5 y 2 , x 4 y 3 , x 3 y 4 , x 2 y 5 , xy6 , y 7 , x 8 , x 7 y, x 6 y 2 , x 5 y 3 , x 4 y 4 , x 3 y 5 , x 2 y 6 , xy7 , y 8 , x9 , x 8 y, x 7 y 2 , x 6 y 3 , x 5 y 4 , x 4 y 5 , x 3 y 6 , x 2 y 7 , xy8 , y 9 , x 10 , x 9 y, x 8 y 2 , x 7 y 3 , x 6 y 4 , x 5 y 5 , x 4 y 6 , x 3 y 7 , x 2 y 8 , xy9 , y 10 , x11 , x 10 y, x 9 y 2 , x 8 y 3 , x 7 y 4 , x 6 y 5 , x 5 y 6 , x 4 y 7 , x 3 y 8 , x 2 y 9 , xy 10 , y11 , x12 , x 11 y, x 10 y 2 , x 9 y 3 , x 8 y 4 , x 7 y 5 , x 5 y 7 , x 4 y 8 , x 3 y 9 , x 2 y 10 , xy 11 , y 12 , x13 , x 12 y, x 11 y 2 , x 10 y 3 , x 9 y 4 , x 8 y 5 , x 5 y 8 , x 4 y 9 , x 3 y 10 , x 2 y 11 , xy12 , y 13 , x14 , x 13 y, x 12 y 2 , x 11 y 3 , x 10 y 4 , x 9 y 5 , x 5 y 9 , x 4 y 10 , x 3 y 11 , x 2 y 12 , xy13 , y14 , x 15 , x 14 y, x 13 y 2 , x 12 y 3 , x 11 y 4 , x 10 y 5 , x 5 y 10 , x 4 y 11 , x 3 y 12 , x 2 y 13 , xy 14 , y 15 , x 16 , x 15 y, x 14 y 2 , x 13 y 3 , x 12 y 4 , x 11 y 5 , x 5 y 11 , x 4 y 12 , x 3 y 13 , x 2 y 14 , xy 15 , y 16 , x 17 , x 16 y, x 15 y 2 , x 14 y 3 , x 13 y 4 , x 12 y 5 , x 5 y 12 , x 4 y 13 , x 3 y 14 , x 2 y 15 , xy 16 , y 17 , x 18 , x 17 y, x 16 y 2 , x 15 y 3 , x 14 y 4 , x 13 y 5 , x 5 y 13 , x 4 y 14 , x 3 y 15 , x 2 y 16 , xy 17 , y 18 , x 19 , x 18 y, x 17 y 2 , x 16 y 3 , x 15 y 4 , x 14 y 5 , x 5 y 14 , x 4 y 15 , x 3 y 16 , x 2 y 17 , xy 18 , y 19 , x 19 y, x 18 y 2 , x 17 y 3 , x 16 y 4 , x 15 y 5 , x 5 y 15 , x 4 y 16 , x 3 y 17 , x 2 y 18 , xy 19 , y 20 , x 20 y, x 19 y 2 , x 18 y 3 , x 17 y 4 , x 16 y 5 , x 5 y 16 , x 4 y 17 , x 3 y 18 , x 2 y 19 , xy 20 , x 20 y 2 , x 19 y 3 , x 18 y 4 , x 17 y 5 , x 5 y 17 , x 4 y 18 , x 3 y 19 , x 2 y 20 , xy 21 , x 21 y 2 , x 20 y 3 , x 19 y 4 , x 18 y 5 , x 5 y 18 , x 4 y 19 , x 3 y 20 , x 2 y 21 , x 21 y 3 , x 20 y 4 , x 19 y 5 , x 5 y 19 , x 4 y 20 , x 3 y 21 , x 2 y 22 , x 22 y 3 , x 21 y 4 , x 20 y 5 , x 5 y 20 , x 4 y 21 , x 3 y 22 , x 22 y 4 , x 21 y 5 , x 5 y 21 , x 4 y 22 , x 3 y 23 , x 23 y 4 , x 22 y 5 , x 5 y 22 , x 4 y 23 , x 23 y 5 , x 5 y 23 , x 4 y 24 , x 24 y 5 , x 5 y 24 , x 5 y 25 (8.0) The element l = ax +by ∈ S 1 (V ) G is the strong Lefschetz element if and only if 21 i=1g i = 0, where g i is a polynomial in a, b given by g 1 (a, b) = a , g 2 (a, b) = b , g 3 (a, b) = a 2 + ab − b 2 , g 4 (a, b) = a 2 + b 2 , g 5 (a, b) = a 4 − 3a 3 b + 4a 2 b 2 − 2ab 3 + b 4 , g 6 (a, b) = a 4 + 2a 3 b + 4a 2 b 2 + 3ab 3 + b 4 , g 7 (a, b) = a 4 − 3a 3 b − a 2 b 2 + 3ab 3 + b 4 , g ...…”
unclassified